Forest Enets and Tundra Enets : how different are they and why? - Khanina, Olesya; Shluinsky, Andrey (Helsingin yliopiston kirjasto, 2022)
With this paper, we aim to summarize linguistic facts on the similarity or the difference between the two Enets lects. Indeed, a full account of the linguistic differences between the two Enets has never been provided. Scholars of Enets have referred to a handful of evident diverging reflexes of Proto-Northern-Samoyed phonemes and a dozen of non-cognate lexemes with identical meanings, without going any further (Prokof’ev 1937; Tereščenko 1966; Helimski 1984/2000). The grammatical features of Forest and Tundra Enets have never been systematically compared.